Transfer of Semibatch Processes to Continuous Processes with Side Injections—Opportunities and Limitations. Issue 4 (20th June 2016) - Goerke, Thilo; Kohlmann, Daniel; Engell, Sebastian
Abstract : The transferability from semibatch to continuous mode of operation is investigated by the detection of the ranges of feasible processes in both modes of operation. A comparison of the resulting ranges in terms of certain product qualities enables the prediction of transferable reaction systems. Abstract : The transfer of copolymerization processes from discontinuous plants to continuous plants has become a topic of industrial interest in the recent years. The motivations for such a transfer are better product consistency, smaller capital investment, and smaller footprint of the plants. However the experiences of the F3 project show that some copolymerization processes cannot be transferred to continuous production if the product quality must remain the same because in a continuous reactor, feeds can be added only at certain points along the reactor. This paper discusses the transferability of semibatch polymerization processes to a continuous plug‐flow reactor with side injections in a generic fashion. Transferability of a semibatch recipe here means the possibility of the production of the same product in both modes of operation (semibatch and continuous). To determine the limits of the transferability from semibatch to continuous production, a model‐based analysis has been performed based on a simplified kinetic model and realistic kinetic parameters. The ranges of product qualities that can be produced in both modes of operation and the minimum changes in the product qualities, if no 1:1 transfer is possible are determined by means of model‐based optimization. Besides the numerical results, also an analytical treatment is presented. This provides a sound basis for an analysis of the transferability from a kinetic and an economic point of view.